FACTOR INFLUENCING COMMUNITY PARTICIPATION IN WASTE BANKS DURING COVID-19 IN CILEGON CITY, BANTEN INDONESIA - Nurce Arifiati; Fauzul Hayat (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
In Indonesia, achieving community participation in waste management continues to be quite difficult. In Cilegon City, Banten, the management of solid waste at the local level requires the use of a waste bank. In Cilegon City, Banten, during COVID-19, this study sought to identify the contributing elements to community engagement in waste banks. Cross-sectional research is the method used in this study. The findings indicated that 60% of respondents struggled to participate in garbage banks. Female respondents made up 54% of the sample, and 64% of them were over 30 years old. Gender had a very strong impact on community involvement in waste banks (OR = 4.500; 95% CI: 1.862-10.877). Additionally, other variables such as attitude level (OR = 3.444; 95% CI: 1.403-8.457) and family influence this community participation. Female gender, attitude, and family support were the primary factors that significantly influenced community engagement in waste banks in Cilegon City. Therefore, a policy change that emphasizes female empowerment is required to enhance the current method of managing solid waste at the community level.